1990
DOI: 10.1002/pi.4980220408
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric surfactants for enhanced oil recovery. IV—Thermodynamic properties of ethoxylated alkylphenol formaldehyde polymeric surfactants

Abstract: The thermodynamic properties of some low molecular weight ethoxylated alkylphenol formaldehyde polymeric surfactants have been investigated. Surface tension as a function of concentration of the surfactants in aqueous solutions was measured at 28, 38, 48 and 58"C, using the spinning drop technique.From these measurements, the minimum area per molecule at the aqueous solution/air interface (Amin) was determined. The thermodynamic parameters of micellization (AG,,,, AH,,,,, ASmlc) and of adsorption (AGdd, AH,,, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The listed data show that the CMC decreases with increasing number of ethylene oxide units (n), hydrophilic± lyophilic balance (HLB) and measuring temperature for the investigated non-ionic monomeric and polymeric surfactants. This ®nding runs in harmony with the data published by Yousef et al 20 and Calderara et al 21 who suggested that the reduction in CMC values is due to the decrease in the solubility of the surfactants. This behaviour may result from a coiling of polyethylene oxide chains due to the decrease in the solubility of the ethoxylated surfactants.…”
Section: Surface and Thermodynamic Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…The listed data show that the CMC decreases with increasing number of ethylene oxide units (n), hydrophilic± lyophilic balance (HLB) and measuring temperature for the investigated non-ionic monomeric and polymeric surfactants. This ®nding runs in harmony with the data published by Yousef et al 20 and Calderara et al 21 who suggested that the reduction in CMC values is due to the decrease in the solubility of the surfactants. This behaviour may result from a coiling of polyethylene oxide chains due to the decrease in the solubility of the ethoxylated surfactants.…”
Section: Surface and Thermodynamic Parameterssupporting
confidence: 85%
“…The values of the ef®ciency (pC 20 ) for the studied surfactants are also given in Table 3. These data reveal that Π CMC decreases with increasing temperature while pC 20 increases with increasing temperature and with the value of n.…”
Section: ±28mentioning
confidence: 99%
“…The large negative DG°m ic contributed to the change in entropy of the system. There are two basic opposing structural processes which occur during micellization [34]: (I) destruction of the iceberg like structured water molecules, known as ''flickering clusters'', surrounding the hydrocarbon chain that leads to a positive entropy change, and (II) rearrangement of randomly oriented monomers into micelles that leads to a negative entropy change. The data in Table 5 shows that the DS°m ic values are all positive indicating that micelle formation is favored by entropy gain [31].…”
Section: Thermodynamic Parameters Of Micellization and Adsorptionmentioning
confidence: 99%